Different newspapers - different inflation perceptions - Arndt, Sarah (AWI discussion paper series, 2024)
In this paper, I investigate how inflation signals from different types of newspapers influence household inflation expectations in Germany. Using text data and the large language model GPT-3.5-turbo-1106, I construct newspaper-specific indicators and find significant heterogeneity in their informativeness based on the genre-tabloid versus reputable sources. The tabloid's indicator is more effective for predicting perceived inflation among low-income and lower-education households, while reputable newspapers better predict higher-income and more educated households' expectations. Local projections reveal that tabloid sentiment shows an immediate decrease following a monetary policy shock, whereas responses from reputable newspapers are smaller and delayed. Household expectations also vary depending on the type of newspaper affected by the sentiment shock and the socioeconomic background of the household. These findings underscore the differentiated impact of media on inflation expectations across various segments of society, providing valuable insights for policymakers to tailor communication strategies effectively.
Keywords: Graue Literatur